The first complete genome of Fructilactobacillus vespulae: strain Mu01, isolated from nectar of Musa paradisiaca L. - Manuel Zúñiga; Cristina Alcántara; Ángela Peirotén; Luis Andrés Ramón-Nuñez; Vicente Monedero; José María Landete (BMC Genomic Data)
Abstract Objectives Lactobacillales, commonly known as lactic acid bacteria (LAB), is an order of Gram-positive, facultatively anaerobic or microaerophilic bacteria characterized by their ability to ferment carbohydrates and produce lactic acid as a major metabolic byproduct. Many species within this group have significant roles in food fermentation, human health, and industrial applications. Here, we report the complete genome sequence of Fructilactobacillus vespulae Mu01, the first sequenced genome of this species. The complete genome sequence of F. vespulae Mu01 is expected to provide valuable insights into the genetics and metabolism of this little-characterized species. Data description A novel strain of Fructilactobacillus vespulae was isolated from nectar of Musa paradisiaca L. during a survey for LAB associated with wild and cultivated plants in the metropolitan area of Valencia, Spain. A complete genome was obtained by sequencing with Nanopore long read technology. The genome consists of a chromosome of 1506092 bp and a plasmid of 42437 bp, presenting a GC content of 36 % and 31 %, respectively. The genome includes 1541 genes, with 1450 CDSs, 7 pseudogenes, 18 rRNA encoding genes, 63 tRNAs and 3 ncRNAs.